Unveiling the Burden of Osteoporosis: Exploring the Prevalence and Risk Factors among Postmenopausal Women in North Central Bangladesh. (Central Medical College Journal, 2024)
Background: Osteoporosis affects 30% of women globally between the ages of 40 and 50. This disease is among the top causes of death and disability among the elderly. This study aimed to examine the prevalence of primary osteoporosis and poor bone density in postmenopausal women, as well as their socio demographic, obstetric, and lifestyle risk factors.Aim: The purpose of this study is to investigate at the prevalence of osteoporosis and the risk factors linked with it in postmenopausal women.Methods: The present prospective cross-sectional study was conducted on postmenopausal women who visited orthopedics, gynecology, and medicine outpatient departments between August 2022 and March 2023; 539 women aged 45 to 80 years with verified menopause were recruited. The final recommendation was for 539 women to have bone mineral density testing utilizing dual energy X-ray absorptiometry. Socio-individual, obstetric-medical, short-form physical activity, and anthropometric questionnaires were administered. Chi-square and Student's t-tests were applied to categorical and continuous data, respectively, to assess the differences between the groups. In SPSS 26, P